Cyclometallation of a germylene ligand by concerted metalation-deprotonation of a methyl group - Bakthavachalam, K.; Dutta, Sayan; Arivazhagan, C.; Raghavendra, Beesam; Haridas, Anagha; Sen, Sakya S.; Koley, Debasis; Ghosh, Sundargopal (Dalton Transactions, 2018)
The reaction of [CH{(CMe)(2,6-iPr(2)C(6)H(3)N)}(2)]GeCl with LiN(SiMe3)(2) was previously reported, which led to the formation of a hetero-fulvene type germylene, [CH{(CMe)(C?CH2)(2,6-iPr(2)C(6)H(3)N)}(2)]Ge through the deprotonation of the C-H bond from the methyl substituents. In this paper, we attempted the analogous reaction with (Dipp)NCMeCHCOMeGeCl using LiN(SiMe3)(2) which gave rise to a metathesis product, (Dipp)NCMeCHCOMeGeN(SiMe3)(2) (2). However, the reactions of 2 with [M2Cl2(-Cl)(2)((5)-Cp*)(2)] (M = Rh and Ir) resulted in cyclometallated Rh and Ir complexes through the activation of the C-H bond from the germylene ligand. The complexes were characterized by single crystal X-ray analysis, which authenticated the presence of Ge-Rh and Ge-Ir bonds. DFT studies have been performed to understand the mechanism.